Associations of Maternal Fructosamine before Delivery in Gestational Diabetes Mellitus Pregnancies with Neonatal Glucometabolic Disorders - Zhengxia Mao; Ruilin Wu; Huan Yu; Yujiao Zhang; Wenbin Dong; Lile Zou; Xiaoping Lei (Journal of Diabetes Research)
Background. The offspring of pregnant women with gestational diabetes mellitus (GDM) are vulnerable to be glucometabolic disorders. However, to date, few current studies focused on the associations of maternal accumulated glucose exposure before delivery with neonatal glucometabolic disorders and large for gestational age (LGA) infants. This study is aimed at exploring the associations of maternal fructosamine (FMN) before delivery in GDM pregnant women with neonatal glucometabolic disorders in the first 3 days of life and LGA infants. Methods. The study subjects were the GDM pregnant women, who gave birth in our hospital from September 1, 2018 to January 31, 2021, and their newborns. The maternal FMN adjusted by serum albumin (FMNALB) before delivery was selected as exposure factors. A multivariate logistical regression model was used to calculate the odds ratios (OR) for neonatal glucometabolic disorders, hypoglycemia needing intervention (<2.6 mmol/L), and glucose intolerance (>7.0 mmol/L) in the first 3 days and LGA infants. Results. In GDM pregnant women, the newborns in the maternal FMNALB≥75th percentile (≥5.89 mmol/g) group had higher risks in neonatal glucometabolic disorders (aOR 2.50, 95% CI 1.34-4.65, P=0.004) and hypoglycemia (aOR 2.18, 95% CI 1.16-4.10, P=0.016). However, FMNALB≥75th percentile seemed to be not predictive of the glucose intolerance (aOR 1.76, 95% CI 0.82-3.79, P=0.149) and LGA (aOR 1.56, 95% CI 0.81-3.02, P=0.185). Further, in the sensitivity analysis, the newborns in the maternal FMNALB≥90th percentile (≥6.40 mmol/g) group also had higher risks in neonatal glucometabolic disorders (aOR 5.70, 95% CI 2.18-14.89, P<0.001) and hypoglycemia (aOR 3.72, 95% CI 1.48-9.31, P=0.005). Conclusions. The maternal FMNALB before delivery in GDM pregnant women was a useful biomarker to identify the offspring with high risk of neonatal glucometabolic disorders. However, the association between maternal FMNALB and the risk of LGA infants was not so strong.